Endotracheal metastasis of hepatocellular carcinoma: a case report - Giacomo Ghinassi; Pasquale Imitazione; Alfonso Pecoraro; Luciano B. G. Montella; Paola Martucci; Raffaella Giacobbe; Campione Severo; Domenico Aronne (Multidisciplinary Respiratory Medicine, 2019)
Abstract We describe the case of a 75 years old patient with a history of hepatocellular carcinoma, with acute respiratory failure due to tracheal obstruction by metastasis, successfully treated with airway disobstruction with rigid bronchoscope.